Influence of the addition of microsphere load amoxicillin in the physical, chemical and biological properties of an experimental endodontic sealer. (January 2018) - Dornelles, Nélio Bairros; Collares, Fabrício Mezzomo; Genari, Bruna; de Souza Balbinot, Gabriela; Samuel, Susana Maria Werner; Arthur, Rodrigo Alex; Visioli, Fernanda; Guterres, Silvia Stanisçuaski; Leitune, Vicente Castelo Branco
Abstract: Aim: To develop an endodontic sealer with amoxicillin-loaded microsphere and to evaluate its properties. Methods: Experimental sealer was obtained by mixing 70 wt% UDMA, 15 wt% GDMA and 15 wt% BISEMA. In addition, CQ, DHEPT and PB were incorporated at 1 mol% and 0.01 wt% BHT and 10 wt% YbF3. Microspheres were produced by drying in spray dryer. Two experimental groups (10 and 15 wt% of microspheres) and one control group (without microspheres) were formulated. The sealers were evaluated for the degree of conversion (n = 3), degradation in solvent (n = 3), drug release profile (n = 3), antimicrobial activity (n = 3), flow (n = 3), film thickness (n = 3) and cytotoxicity (n = 3). Data were analyzed by ANOVA and Tukey with significance level of 5%. Results: Microespheres presented a mean size of 2.664 μm. Immediate degree of conversion ranged from 51.73% to 55.13% and the 24 h degree of conversion ranged from 60.79% to 73.80%. Upon solvent degradation 54.44% and 56.21% reduction in hardness were observed for 10% and 15% concentrations respectivelly. The drug release profile showed an average release of 73.76% of the drug in 96 h. Significant reduction in antimicrobial activity was observed for 10% concentration after 24 h, 48 h and 96 h compared to control. The flow and film thickness showed values in accordance to the ISO 6876. Cytotoxicity showed high cellular viability. Conclusion: The addition of up to 10% of microspheres containing amoxicillin presented antimicrobial activity and did not alter the properties of the experimental endodontic cement. Clinical significance: Amoxicillin microspheres with its antimicrobial activity in root canal sealers could reduce reintervations in endodontics when persistent bacteria or reinfection takes place in root canal system.